1980
DOI: 10.1128/iai.28.1.127-131.1980
|View full text |Cite
|
Sign up to set email alerts
|

Depressed immunological defence mechanisms in mice with experimentally induced diabetes

Abstract: Persistent diabetes mellitus with marked hyperglycemia was induced in mice by the administration of streptozotocin. In these streptozotocin-induced diabetic mice, resistance to tubercle bacillus challenge and primary as well as secondardy humoral immune responses against foreign erythrocytes were markedly depressed. The T-cell function in delayed hypersensitivity to 2,4-dinitro-1-fluorobenzene and bacterial phagocytic activity or peritoneal macrophages were markedly depressed. In contrast, the B-cell function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 15 publications
(14 reference statements)
1
31
0
Order By: Relevance
“…This reduced expression correlated well with the impaired host resistance to this infection. In an earlier study, Saiki et al [6] demonstrated that diabetic mice established by administration of STZ exhibited weaker delayed-type hypersensitivity to PPD and were more prone to M. tuberculosis infection than control nondiabetic mice. However, these findings were not followed-up to define the mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…This reduced expression correlated well with the impaired host resistance to this infection. In an earlier study, Saiki et al [6] demonstrated that diabetic mice established by administration of STZ exhibited weaker delayed-type hypersensitivity to PPD and were more prone to M. tuberculosis infection than control nondiabetic mice. However, these findings were not followed-up to define the mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…These immunological parameters became normal following successful therapies [9]. In addition, macrophage functions including bacterial phagocytic capacity, resistance to tubercle bacilli and T cell function in delayed type hypersensitivity, were also depressed in mice with experimentally induced diabetes [10]. These studies suggest that the functions of both T cells and macrophages are compromised in diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Streptozotocin may strongly depress the host immune systems for bacterial translocation. However, Saiki et al (12) reported that T-cell function and phagocytic activity in macrophages were depressed in streptozotocin-induced diabetic mice, both of which may reflect metabolic disturbance rather than direct toxic effects of streptozotocin to the host. Suppressed cell-mediated immunity in streptozotocin-incluced diabetes reverts to normal with insulin therapy (9).…”
mentioning
confidence: 99%